Comparative effects of recovery strategies on exercise-induced muscle fatigue:a randomized controlled trial - Wei, Ming; Shen, Xudong; Wang, Siyu (Frontiers in Physiology, 2025)
ObjectiveThis study aimed to compare the effects of five post-exercise recovery interventions—massage, cold-water immersion (CWI), vibration therapy, functional electrical stimulation (FES), and static stretching—on central nervous modulation, neuromuscular function recovery, and inflammatory response following exercise-induced muscle fatigue (EIMF).MethodsThis randomized controlled trial employed a two-way repeated-measures analysis of variance (ANOVA; group × time) to evaluate the effects of different recovery interventions over time. Thirty healthy male participants were randomly assigned to six groups (n = 5 each): massage (Group A), CWI (Group B), vibration therapy (Group C), static stretching (Group D), FES (Group E), and control (Group F). EIMF was induced using a standardized exercise model. Physiological and biochemical measurements were taken at baseline, immediately post-exercise, and at 24, 48, and 72 h. Physiological indicators included muscle contraction time (TC), maximal radial displacement (DM),peak concentric power, The blood biochemical indicators include gamma-aminobutyric acid (GABA), creatine kinase (CK),and interleukin-6 (IL-6).ResultsVibration therapy demonstrated a significant advantage in reducing TC at 72 h post-exercise (p = 0.027,p < 0.05); Although no statistically significant differences were found for DM,the massage group showed a more favorable recovery trend; FES significantly improved peak concentric power at 48 h post-exercise (p = 0.000, p < 0.01). Massage significantly increased GABA levels (p = 0.001, p < 0.05) and reduced CK concentrations (p = 0.000, p < 0.01) at 48 h. CWI demonstrated a significant inhibitory effect on IL-6 at 48 h (p = 0.000, p < 0.01).ConclusionMassage therapy showed favorable effects in central modulation and muscle repair. CWI effectively controlled acute inflammation. FES improved muscle explosive power, while vibration therapy enhanced neuromuscular responsiveness. Static stretching group showed no significant recovery benefit, as stretching primarily enhances ROM and flexibility and has only limited impact on the critical physiological pathways necessary for EIMF recovery.